NUTRITIONAL AND ROTI QUALITY OF SORGHUM GENOTYPES - U.D. Chavan; J.V. Patil; M.S. Shinde (Indonesian Journal of Agricultural Science, 2009)
Sorghum grains are mostly used for the roti preparation. The M 35-1 (Maldhandi) a sorghum cultivar is known for its good quality of roti due to having pearly white grain color, its flour having higher water holding capacity, and good organoleptic taste. However, this cultivar is low yielder. To evolve sorghum high yielding genotype coupled with this good roti qualities, systematic breeding program was planned and executed to overcome this problem. Twenty local land races, 92 genotypes, and seven improved cultivars of sorghum along with check M 35-1 were studied for various nutritional quality parameters, with special reference to the roti quality. Considering nutritional quality and organoleptic evaluation parameters studied for roti quality, the local land races viz., RSLG 428-1, RSLG 1238, RSLG 1275 and the genotypes viz., RSV 290, RSV 292, RSV 858, RSV 859, RSV 861, RSV 868, RSV 894, RSV 985, RSV 992, RSV 995, RSV 999 were found to be promising for protein, sugar, water absorption, and soluble protein content. Therefore, they can be used for further improvement in nutritional quality through breeding program. Among the improved cultivars, Phule Vasudha (RSV 423), CSV 22, and Phule Chitra (SPV 1546) werefound to be most promising for roti quality. The maximum score for overall acceptability was found for Phule Vasudha followed by Phule Anuradha (RSV 458), Phule Yeshoda (RSLG 262), and Phule Maulee (CSV 216).